Evaluation of corona virus disease (COVID-19) surveillance system in Yogyakarta District, 2020 - Fitriani, Bhekti (BKM Public Health and Community Medicine, 2021)
Objective: Implementing a surveillance system is one of effort to monitor trends and contain outbreaks. This evaluation had been done for the first time to describe the performance of COVID-19 surveillance system in Yogyakarta District and provide recommendations. Method: This study type was a descriptive evaluation study. Surveillance data COVID-19 routinely collected from data managers since March 16 to September 20, 2020. The interview was conducted to 5 epidemiologists in Yogyakarta District of Health. The indicators of evaluation were simplicity, flexibility, completeness, acceptability, positive predictive value, representativeness, and timeliness. Results: A total of 18 PHCs, 7 COVID-19 referral hospitals, and 2 non-referral COVID-19 hospitals reported confirmed cases. A total of 333 confirmed cases were recorded during the evaluation. The median age of confirmed cases was 43 years (range: 2–84 years) of which 54% were male. The highest case was from Umbulharjo sub district namely 21% (70/333). Positive predictive value was 7.4% that was still above standard value of guidelines, namely <5%. The completeness of the data from the data manager was 90% (301/333). Average time between reports received by the health office and the date of laboratory confirmation results is 1 day (range: 0-8 days). The greatest strength of the system was acceptability and representativeness. Conclusions: The quality of COVID-19 surveillance data has not met the aspect of positive predictive value and completeness. Increased weekly specimen tests should be done and an investigation report could be a source of data to complete the data in the data manager.